2007
DOI: 10.1002/ijc.22998
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling pathway is inactive in colorectal cancer cell lines

Abstract: The Hedgehog (Hh) signaling pathway plays an important role in human development. Abnormal activation of this pathway has been observed in several types of human cancers, such as the upper gastro-intestinal tract cancers. However, activation of the Hh pathway in colorectal cancers is controversial. We analyzed the expression of the main key members of the Hh pathway in 7 colon cancer cell lines in order to discover whether the pathway is constitutively active in these cells. We estimated the expression of SHH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
(46 reference statements)
3
44
2
Order By: Relevance
“…In agreement with previous observations in medulloblastoma cell cultures and serum-cultured colon cancer cells (25,26), the expression of downstream mediators of Shh pathway in NSCs and medulloblastoma CSCs was modest, and, accordingly, Shh pathway activation was marginally relevant for proliferation and self-renewal of NSC/CSCs (27) as well as in CSCs isolated from the same Ptch mouse model (28) or other brain tumors (29). Indeed, both NSC/CSC-derived neurospheres employed in those studies were maintained in vitro for very few subculturing passages.…”
Section: Molecular Analysis Of Medulloblastoma-derived Cscs and Hindbsupporting
confidence: 81%
“…In agreement with previous observations in medulloblastoma cell cultures and serum-cultured colon cancer cells (25,26), the expression of downstream mediators of Shh pathway in NSCs and medulloblastoma CSCs was modest, and, accordingly, Shh pathway activation was marginally relevant for proliferation and self-renewal of NSC/CSCs (27) as well as in CSCs isolated from the same Ptch mouse model (28) or other brain tumors (29). Indeed, both NSC/CSC-derived neurospheres employed in those studies were maintained in vitro for very few subculturing passages.…”
Section: Molecular Analysis Of Medulloblastoma-derived Cscs and Hindbsupporting
confidence: 81%
“…As PTCH and GLI1 were indicators of Hh pathway activity, He concluded that the Hh pathway was not active in these CRC cell lines (Yoshikawa et al, 2009). Chatel analyzed the gene and protein expressions DOI:http://dx.doi.org/10.7314/APJCP.2012.13.5.2319 of the main key members of the Hh pathway (SHH, IHH, PTCH, SMO, GLI1, GLI2, GLI3, SUFU and HHIP) in 7 colon cancer cell lines and found none of them expressed the complete set of Hh pathway members (Chatel et al, 2007). However, by analyzing CRC cell lines as well as human tissues from 40 patients with local or metastatic CRCs, Varnat found consistent expression of PTCH, GLI1 and SHH as well as other Hh-GLI1 pathway components.…”
Section: Discussionmentioning
confidence: 99%
“…The data about the roles they play on CRC have not been well documented. Some of them even remained controversial (Berman et al, 2003;Douard et al, 2006;Monzo et al, 2006;Chatel et al, 2007;Varnat et al, 2009; 2320 Yoshikawa et al, 2009;Fu et al, 2010;Saqui-Salces and Merchant, 2010;You et al, 2010;Tapati et al, 2011). There were disagreements in the roles of downstream Hh signaling components i.e.…”
Section: Expression and Clinical Significance Of Hedgehog Signaling Pmentioning
confidence: 99%
“…Paracrine signaling was further verified in xenografts with human cell lines and cancer biopsies in mice [18]. According to Chatel and co-workers, activation of Hh pathway is not a common event in cultured cells [19]. However, several other studies have addressed the essential role of epithelial Hh signaling in CRC development, growth, stem cell renewal, and metastatic behavior in advanced cancer [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 96%